Sensorial and chemical analysis of biscuits prepared by incorporating Moringa flower powder and leaf powder - Yadav KC (International Journal of Food Properties, 2022)
Moringa oleifera is a nutrient-rich plant, also referred to as a miracle tree, and is commonly used in the preparation of functional foods including herbal biscuits. Despite having a wide range of biomolecules, M. oleifera has not been studied for its nutritional benefits in Nepal. To fill this gap, five different formulations of flower and leaf powder ratios of 11:4, 11.75:3.25, 12.5:2.5, 13.25:1.75, 14:1 named as A, B, C, D, E, and control formulations were tested for their sensory and chemical characteristics. The results showed that calcium content (115.73 mg/100 g) was higher in biscuits with a higher percentage of the leaf (11:4) while TPC was minimum. Further, biscuits containing a higher percentage of flower powder contained fewer tannins. The sensory analysis concluded that D was deemed the best in overall attributes by panelists upon statistical analysis, however formulations A and B were superior to other samples regarding the chemical properties. These findings confirm that there is a huge potential for improving herbal biscuits.